Crosstalk between cancer stem cells and myeloid-derived suppressor cells: implications for tumor progression and immunotherapy - Wang, Bo; Zhao, Xiaoguo; Han, Shuxin; Xu, Yuekang; Li, Jinyao (Frontiers in Immunology, 2025)
Cancer stem cells (CSCs) represent a small subset of tumor cells populations characterized by their ability to self-renew and differentiate. These cells are often considered resistant to chemotherapy, radiotherapy, and immunotherapy, playing a crucial role in driving tumor progression and metastasis. To evade immune attacks, CSCs utilize various genetic and epigenetic strategies that diminish immune recognition, enhance tolerance to immune-induced cytotoxicity, and foster the development of a protective immunosuppressive microenvironment. This microenvironment is shaped by a group of key immunosuppressive cells, particularly myeloid-derived suppressor cells (MDSCs), which not only directly inhibit effector T cells and natural killer (NK) cells, facilitating the immune escape of CSCs, but also significantly contribute to the maintenance of tumor cell stemness and promote their metastasis. Conversely, the developmental signals of MDSCs are also regulated by CSCs. This complex interplay between MDSCs and CSCs adds layers of complexity to the cancer-immune cycle and the associated tumor treatment strategies. Therefore, understanding the detrimental interdependence between MDSCs and CSCs to effectively impede tumor progression has become heated topic in tumor immunology. In this review, we provide a timely summary of the latest studies on the reported characteristics of CSCs and MDSCs, discuss their interconnection during tumor progression, and evaluate various immunotherapeutic strategies targeting these cell populations.